2017
DOI: 10.1038/s41598-017-12434-z
|View full text |Cite
|
Sign up to set email alerts
|

Group III phospholipase A2 promotes colitis and colorectal cancer

Abstract: Lipid mediators play pivotal roles in colorectal cancer and colitis, but only a limited member of the phospholipase A2 (PLA2) subtypes, which lie upstream of various lipid mediators, have been implicated in the positive or negative regulation of these diseases. Clinical and biochemical evidence suggests that secreted PLA2 group III (sPLA2-III) is associated with colorectal cancer, although its precise role remains obscure. Here we have found that sPLA2-III-null (Pla2g3 −/−) mice are highly resistant to colon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 82 publications
0
32
0
Order By: Relevance
“…PLA2G2F sPLA 2 -IIF Suprabasal keratinocytes Production of lysoplasmalogen Protection from psoriasis, CHS and skin cancer Spontaneous development of psoriasis-like epidermal hyperplasia and alopecia, Exacerbation of skin cancer [45] PLA2G3 sPLA 2 -III Epididymal epithelial cells Sperm membrane phospholipid remodeling Male hypofertility N.D. [93] Mast cells Production of microenvironmental PGD 2 Impaired mast cell maturation and anaphylaxis Increased mast cell maturation and anaphylaxis [34] Colonic epithelial cells Production of LPA and LPI Protection from colonic cancer and colitis N.D. [92] Aorta a Generation of LPC-rich small-dense LDL N.D.…”
Section: Pe and Ps)mentioning
confidence: 99%
See 4 more Smart Citations
“…PLA2G2F sPLA 2 -IIF Suprabasal keratinocytes Production of lysoplasmalogen Protection from psoriasis, CHS and skin cancer Spontaneous development of psoriasis-like epidermal hyperplasia and alopecia, Exacerbation of skin cancer [45] PLA2G3 sPLA 2 -III Epididymal epithelial cells Sperm membrane phospholipid remodeling Male hypofertility N.D. [93] Mast cells Production of microenvironmental PGD 2 Impaired mast cell maturation and anaphylaxis Increased mast cell maturation and anaphylaxis [34] Colonic epithelial cells Production of LPA and LPI Protection from colonic cancer and colitis N.D. [92] Aorta a Generation of LPC-rich small-dense LDL N.D.…”
Section: Pe and Ps)mentioning
confidence: 99%
“…Evaluation of the enzymatic property using a lipidomics-based natural membrane assay with a mixture of colon-extracted phospholipids as the substrate has demonstrated that sPLA 2 -III hydrolyzes all phospholipid subclasses including PC, PE, PS, PI and PG (i.e. with no apparent polar head group specificity), tending to prefer the sn-2 position of PUFAs [92]. In mice, sPLA 2 -III is distributed in several tissues, showing the highest expression in the colon, skin, and male reproductive organs [92,93].…”
Section: General Aspectsmentioning
confidence: 99%
See 3 more Smart Citations